PKM TEKNOLOGI MESIN PENGASAP BAGI PENGUSAHA IKAN ASAP DUSUN PALODEM DESA TEMBOKREJO MUNCAR BANYUWANGI - Afandi, Akhmad; Lusi, Nuraini; Hilmi, Mustofa; Diansah, Danang Putra; Hartanto, Abdi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2019)
In general, the smoke fish Processing Society is a society with a lack of knowledge, so that the smoking equipment is not equipped with chimneys because of the expensive production cost, the marination using a simple tool-less Practical and unproductive. So, it is necessary to develop a semi-modern fumigation technology and the community is easy to use. Smoking cabinet utilization as an alternative to environmentally friendly smoking methods is the time to apply in Indonesia. The problem faced by partners in the process of the daily fish smoking worker using the extra power to back the smoked fish, the coal fan and the harmful for the worker is the smoke issued by the fuel so that it can Interfere with the worker's breathing and make sore eyes. By looking at the conditions in the community in processing the smoked fish are done in a traditional and long time, so the need for a more efficient fish-sucking equipment, to help improve the process of smoking fish and reducing air pollution. From the results of this devotion produced a fish smoke machine with a capacity of 10 kg, 60 Watt motor power with an average temperature of 76oC. This smoke machine can reduce the moisture content contained in fish by approximately 10%. Besides, the partners understand the use and maintenance of equipment and with such tools can reduce air pollution.